2020
DOI: 10.3390/pathogens9121002
|View full text |Cite
|
Sign up to set email alerts
|

Gut Symbiotic Microbial Communities in the IUCN Critically Endangered Pinna nobilis Suffering from Mass Mortalities, Revealed by 16S rRNA Amplicon NGS

Abstract: Mass mortality events due to disease outbreaks have recently affected almost every healthy population of fan mussel, Pinna nobilis in Mediterranean Sea. The devastating mortality of the species has turned the interest of the research towards the causes of these events. After the haplosporidan infestation and the infection by Mycobacterium sp., new emerging pathogens have arisen based on the latest research. In the present study, a metagenomic approach of 16S rRNA next generation sequencing (NGS) was applied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…A previous study found strong shifts in unionid gut microbiome composition when comparing wild Ohio pigtoe ( Pleurobema cordatum ) to individuals held in mesocosms under conditions known to induce wasting syndromes and mortality, with shifts to dominance by Proteobacteria in the latter [ 34 ]. Proteobacteria were also the most abundant taxa in the gut bacterial communities of the marine bivalve P. nobilis during a mass mortality event in the Mediterranean Sea [ 26 ]. Based on both prevalence and percent composition, SV2 ( Yokenella/Salmonella ) and SV4 ( Aeromonas spp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found strong shifts in unionid gut microbiome composition when comparing wild Ohio pigtoe ( Pleurobema cordatum ) to individuals held in mesocosms under conditions known to induce wasting syndromes and mortality, with shifts to dominance by Proteobacteria in the latter [ 34 ]. Proteobacteria were also the most abundant taxa in the gut bacterial communities of the marine bivalve P. nobilis during a mass mortality event in the Mediterranean Sea [ 26 ]. Based on both prevalence and percent composition, SV2 ( Yokenella/Salmonella ) and SV4 ( Aeromonas spp.)…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ], and opportunistic Vibrio spp. [ 26 ]. Infectious disease outbreaks in marine bivalves are most often driven by interactions among host factors, abiotic environmental conditions, and pathogens [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disease aetiology of mass mortality events in P. nobilis species is considered a complex situation, involving many microorganisms in relation to rapid changes in abiotic factors due to ongoing climate change [ 21 ]. Infection by H. pinnae was adopted as a main causative agent in many cases without taking into consideration the pathobiome of the species [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…belonging to the Splendidus and Mediterranei clades were detected during mortality events in P. nobilis populations. Experimental laboratory conditions detecting the infection of P. nobilis by Vibrio spp have transformed the phenomenon of mortalities into a complicated matter [ 8 , 19 , 20 , 21 , 22 ]. Investigation of P. nobilis mortalities continued and more potential threats were implicated in the devastation of its natural populations [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ], were analyzed, and revealed the presence of 14 different bacterial OTUs, among which were bacterial genera such as Vibrio sp., Mycoplasma spp., Pseudoalteromonas spp., Mycobacterium sp., Aliivibrio spp., Photobacterium spp., and Psychrilyobacter spp. [ 31 ]. The aforementioned genera can be symbiotic or pathogenic genera for bivalves, supporting the complexity of mass mortality events.…”
Section: Introductionmentioning
confidence: 99%